2021
DOI: 10.1016/j.neurol.2021.02.234
|View full text |Cite
|
Sign up to set email alerts
|

Deux cas consécutifs de syndrome de Guillain–Barré avec diplégie faciale dans le contexte d’infection avec le virus SARS-CoV-2

Abstract: Introduction La diplégie faciale révélant un syndrome de Guillain–Barré (SGB) est une manifestation neurologique qui émerge comme associée à l’infection virale émergente SARS-CoV-2. Observation Nous rapportons deux cas consécutifs de diplégie faciale en lien avec un SGB. Les patients remplissaient les critères cliniques (diplégie faciale, parésie, paresthésies symétriques des 4 membres et dysautonomie) ou paracliniques (hyperprotéinorachie, profil ENMG de neuropathie dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At a single research on PubMed, more than a dozen cases of GBS after COVID-19 were reported since the beginning of the pandemic, of which 2 consecutive patients with GBS with facial diplegia were reported by our team. 3…”
mentioning
confidence: 99%
“…At a single research on PubMed, more than a dozen cases of GBS after COVID-19 were reported since the beginning of the pandemic, of which 2 consecutive patients with GBS with facial diplegia were reported by our team. 3…”
mentioning
confidence: 99%